2020
DOI: 10.31234/osf.io/nvg4w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of Attachment-Based Family Therapy compared to Treatment as Usual for Depressed Adolescents in Community Mental Health Clinics

Abstract: Background: Major Depressive Disorder (MDD) is a disabling mood disorder, profoundly affecting a large number of adolescent's quality of life. To date, no obvious treatment of choice for MDD in adolescents is available and progress in the treatment of depressed adolescents will have important public health implications. Attachment-Based Family Therapy (ABFT), as the only empirically supported family therapy model designed to treat adolescent depression, aims to repair interpersonal ruptures and rebuild an emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A larger Norwegian randomised controlled trial comparing 16 weeks of ABFT to treatment as usual (TAU) for adolescent depression (clinicaltrials.gov identifier NCT01830088) was conducted to follow up on these findings. Contrary to the primary hypothesis of the trial, ABFT was not found to be superior to treatment as usual ( 22 ). While the findings from these recent trials do not provide evidence that ABFT on average is more effective than treatment as usual or other active comparisons in treating adolescent depression or suicidal ideation, ABFT is a treatment where moderation of effectiveness by parent-adolescent conflict is highly plausible.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…A larger Norwegian randomised controlled trial comparing 16 weeks of ABFT to treatment as usual (TAU) for adolescent depression (clinicaltrials.gov identifier NCT01830088) was conducted to follow up on these findings. Contrary to the primary hypothesis of the trial, ABFT was not found to be superior to treatment as usual ( 22 ). While the findings from these recent trials do not provide evidence that ABFT on average is more effective than treatment as usual or other active comparisons in treating adolescent depression or suicidal ideation, ABFT is a treatment where moderation of effectiveness by parent-adolescent conflict is highly plausible.…”
Section: Introductionmentioning
confidence: 60%
“…Our findings have considerable uncertainty, and the predicted differences in treatment outcome related to parent-adolescent conflict are clinically meaningful ( 47 ) only in the higher and lower quantiles of the distribution of parent-adolescent conflict. This is not surprising, given the overall small average treatment effect in the trial ( 22 ). For mother-adolescent conflict, there is some evidence of a moderator effect.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a recent study, designed to examine the effectiveness of ABFT compared to Treatment as usual (TAU) in reducing depressive symptoms, we found no differences between the two treatment options ( Waraan et al, 2020 ). Neither ABFT nor TAU was efficient in reducing depressive symptoms.…”
mentioning
confidence: 83%